H2S + SO2 produces water-dispersed sulfur nanoparticles for lithium-sulfur batteries. (November 2017) - Liu, Donghai; Zhang, Chen; Xu, Zhao; Zhang, Lei; Lv, Wei; Zou, Xiaolong; Kang, Feiyu; Zhi, Linjie; Cheng, Hui-Ming; Yang, Quan-Hong
Abstract: Sulfur shows totally opposite faces in environmental and energy issues. Sulfur containing gases, H2 S and SO2, are dominant air pollutants, while sulfur plays as the clean energy carrier for Li-Sulfur (Li-S) batteries. Herein, through confining the gaseous comproportionation reaction in water, between H2 S and SO2 that normally produces uncontrollable aggregates, we develop a completely clean approach to convert the air pollutants into water-dispersed sulfur nanoparticle (WDS). The WDS is contaminant-free, size-controllable, and more promisingly solution processable, and is thus ideal for achieving solution hybridization with other materials for various applications. As a typical example, an aqueously fabricated WDS/carbon nanotube composite delivers the theoretical capacity of sulfur at 0.5 A g −1, and a capacity of 750 mAh g −1 even at a high current density of 5.0 A g −1 . In addition to the normal use of sulfur as cathode, a new-concept WDS/carbon interlayer with a low sulfur content has been designed to inhibit the shuttling of polysulfides, greatly improving the cycling performance of the Li-S battery. The proposed approach gives a good example to turning pollutants into clean energy carriers by green chemistry. Graphical abstract: The reaction SO2 + H2 S→S + H2 O, has been used to produce water-dispersed sulfur nanoparticles (WDS), with water as a medium and also the only reaction side product. The WDS is contaminant-free, solution processable and size-controllable, and we have used Li-S batteries as a typical system to demonstrate the advantages of WDS as both an electrode material and an interlayer. Highlights: SO2 + H2 S→S + H2 O, is confined in water to produce water-dispersed sulfur NPs (WDS). WDS is contaminant-free, solution processable and size-controllable. WDS has shown great advantages in Li-S batteries as a model application. It realizes a perfect marriage of pollutant control and energy storage technique.